2006
DOI: 10.1007/s10038-006-0038-9
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 and GST T1 genetic polymorphisms and Raynaud’s phenomenon in French vinyl chloride monomer-exposed workers

Abstract: Occupational vinyl chloride monomer (VCM) exposure can induce Raynaud's phenomenon (RP). However, not all VCM workers developed RP, which suggests an underlying genetic susceptibility. Genetic polymorphisms of glutathione S-transferases (GSTs), involved in VCM metabolism, have been shown to influence certain VCM-related health effects. We have conducted a case-control study of 58 subjects with RP along with 247 subjects without RP, from a population of 305 French workers exposed or formerly exposed to VCM, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…Interestingly, studies of RP patients that were exposed to vinyl chloride monomer (VCM) suggest that the interaction between a certain genetic background and environmental conditions may play a role in increasing the onset of RP in VCM-exposed individuals (Fontana et al, 2006). In 2006, Fontana et al (2006) investigated whether there is an association between polymorphisms in glutathione S -transferase M1 and T1 genes and RP patients exposed to VCM (Fontana et al, 2006).…”
Section: Rp and Genetic Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies of RP patients that were exposed to vinyl chloride monomer (VCM) suggest that the interaction between a certain genetic background and environmental conditions may play a role in increasing the onset of RP in VCM-exposed individuals (Fontana et al, 2006). In 2006, Fontana et al (2006) investigated whether there is an association between polymorphisms in glutathione S -transferase M1 and T1 genes and RP patients exposed to VCM (Fontana et al, 2006).…”
Section: Rp and Genetic Backgroundmentioning
confidence: 99%
“…In 2006, Fontana et al (2006) investigated whether there is an association between polymorphisms in glutathione S -transferase M1 and T1 genes and RP patients exposed to VCM (Fontana et al, 2006). The results showed that the combination of positive genotypes for both genes may increase susceptibility to RP (Fontana et al, 2006).…”
Section: Rp and Genetic Backgroundmentioning
confidence: 99%
“…The vascular endothelial toxicity of vinyl chloride has been shown by angiographic studies of arteries in the hand and by capillaroscopy [104,105]. The prevalence of RP in vinyl chloride workers ranges from 6 to 33% [106]. In 1980 a prospective exposed/non-exposed cohort study showed a strong association between vinyl chloride exposure and RP (P<0.006) [107].…”
Section: Endothelium Damage And/or Neurotoxicitymentioning
confidence: 99%
“…Many studies have investigated the effect of genetic polymorphisms of genes involved in metabolism (CYP2E1, GST, mEH, ALDH2) and DNA repair (XRCC1, XPD; refs. 6,[9][10][11][12][13][14][15]. To the best of our knowledge, however, no studies have been conducted on the effect of genetic polymorphisms of genes involved in cell cycle control.…”
Section: Introductionmentioning
confidence: 99%